An evaluation of mobile factors on emerging mobile grocery applications to improve customer user experience - Cantos, Maria Sabrina B. (Animo Repository, 2022)
In this era of digitization and modernization, almost every person is using mobile phones to maximize their lifestyle and comfort. In addition, the use of mobile applications has completely altered how people today go about their daily lives and accomplish basic tasks. This includes ordering food and shopping for groceries. This study focuses on improving customer user experience on online mobile grocery applications, specifically by studying the mobile design factors that influence the usability of the interface through usability testing. Usability tests are generally performed to identify areas in the product where people struggle, and help researchers and developers gain recommendations for improvement. In the context of this study, usability testing was done to determine the factors that users consider when ordering and purchasing their groceries through mobile applications. For this study, the researchers tested Pandamart, Foodpanda’s on-demand grocery delivery service. Based on the results of the usability tests, the current interface of the case study grocery application shows weaknesses in user experience with regard to the design factors of content organization, clarity of options, quantity of user inputs, and product information, yielding an average difficulty rating of 1.98 and a satisfaction rating of 3.49, which was validated by the below-threshold average SUS score of 64.75, and SUM score of 71.9% due to the number of errors incurred. The methodology of the study follows the Design of Experiments method (DOE) to determine the most important design factors to focus on in the development of alternatives as well as the number of design iterations needed. The development of the design alternatives was based on the data and insights gathered from the usability testing. Based on the results, the main issues to be addressed included content organization, clarity of options, quantity of user inputs, and product information. These are the factors prioritized in generating the design alternatives. With this, 16 design alternatives were developed incorporating the identified design factors, with each design factor tested with two design levels in line with the 2k factorial design. The two levels for content organization are 2-grid column and thumbnail list, the levels for clarity of options are button list and dropdown list, the levels for product information are windowshade and tabs, and the levels for quantity of user inputs are input area and sliding switch. Each proposed design alternative underwent evaluation through usability testing, similar to the initial testing done on the Pandamart application. Using the Design Expert v.11 software, the optimal alternative was selected and the results were then validated through MANOVA analysis. Conclusively, from the usability testing and analysis, prototype 2, with design settings of a grid for content organization, dropdown for clarity of options, windowshade for product information, and input area for quantity of inputs, are found to be the most optimal design settings. For this proposed interface design, the Design Expert results yielded a value of 1.013 for difficulty ratings, 4.768 for satisfaction ratings, and 0.953 for desirability. This interface was validated to be optimal with an SUS score of 77.5, significantly higher than the acceptable level, and an SUM score of 92.6%, improving by 19.69 % and 28.79%, respectively. Redesigning the current Pandamart interface to this proposed interface has improved customer experience, validated by the insights retrieved from the customer journey maps.